(untitled) (Journal of Education and Development, 2025)
Pre-departure orientation for study abroad program is an important part of the study abroad journey of students. However, this aspect of the study abroad program is somehow neglected in the program offering. Few studies have investigated the efficacy of pre-departure orientation for study abroad from the experience of Japanese university students. Therefore, this paper aims to assess the efficacy of study abroad pre-departure orientation by investigating the experiences of Japanese university students’ study abroad journey in two countries. The researcher utilized a descriptive phenomenology approach. An online survey using a semi-structured bilingual questionnaire was conducted between October to December 2024 among ten study abroad participants in Australia and the Philippines. The respondents were comprised of first year to fourth year students from University A and University B. The online survey data was extracted and Japanese responses were translated into English and analyzed thematically. The experience of Japanese university students on pre-departure orientation for study abroad program is grouped into five main themes and 15 sub-themes. The main themes include: (1) the perceived helpfulness and usefulness of the pre-departure activity for study abroad, (2) the main benefit of pre-departure activity for study abroad, (3) challenges during study abroad experience, (4) mechanisms to cope with the study abroad challenges, and (5) suggestions to improve the pre-departure activity for study abroad. The respondents assessed pre-departure orientation concerning their study abroad experience in Australia and the Philippines. The respondents consider information on specific topics about health, security, and leisure as the main points to enjoy their study abroad experience fully. Further research on pre-departure orientation for study abroad should be conducted.